Cybersecurity in health sector: a systematic review of the literature - Catherine Vanessa Peve Herrera; Jonathan Steve Mendoza Valcarcel; Mónica Díaz; Jose Luis Herrera Salazar; Laberiano Andrade-Arenas (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Currently, health centers are being affected by various cyberattacks putting at risk the confidential information of their patients and the organization because they do not have a plan or tools to help them mitigate these cyberattacks, which is important to know what measures to take to protect the privacy of personal data. The present work was carried out under a systematic literature review, which aims to show the importance of cybersecurity in the health sector knowing which tools are the most used and efficient to prevent a cyberattack. A systematic review of 301 articles was carried out, 79 of which are aligned with the objective set, fulfilling the inclusion and exclusion criteria. The search for information was carried out in the Scopus and Dimensions databases. The analysis carried out has resulted in good information that was compiled for the development of this topic, being favorable thanks to the different research of different authors.